Architectural documentation of historic buildings in Cotabato City - Quiray, Therese Ann L. (2015)
Issues regarding underdeveloped and ignored historic buildings in Mindanao are evident in the lack of recognition of their significance and actions taken upon by authorities to come up with a solution. The aim of this study is to identify, document and assess the current conditions of the different historic structures in Cotabato City as means of conservation. The descriptive research was able to document 6 historic structures, The Tamontaka Church, The Old City Hall, Maguindanao Provincial Jail, Old Provincial Capitol, The Old Pendatun Mansion and the Sangguniang Panlungsod. The data gathered by key-informant interviews, ocular inspection and photo documentation were analysed through visual assimilation and synthesis with literature reviews and were able to conclude different methods of conservation based on the current conditions and perceived significance of the buildings. The study concluded that three of the six structures were in need of rehabilitation, two were to be preserved while one was in need of restoration. Aside from the study area, undocumented historic structures within Mindanao may also be used for further studies. Overall, this research was a step towards the conservation of historic structures not only in Mindanao but also in the Philippines.